2001
DOI: 10.1096/fj.00-0784fje
|View full text |Cite
|
Sign up to set email alerts
|

Wnt regulation of limb mesenchymal chondrogenesis is accompanied by altered N‐cadherin‐related functions

Abstract: It has been suggested that Wnt proteins play essential roles in the regulation of limb development and morphogenesis. We have analyzed the effects of RCAS retroviral-mediated misexpression of Wnt-5a and Wnt-7a, two Wnt genes expressed during normal limb development, on chondrogenesis in high-density micromass cultures of chick limb bud mesenchymal cells. Wnt7a misexpression inhibited chondrogenesis in vitro, whereas Wnt-5a did not. Analysis of cellular condensation and precartilage aggregate formation revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
105
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 83 publications
8
105
1
Order By: Relevance
“…Because the transforming group of Wnt family, such as Wnt1 and Wnt7a, but not nontransforming Wnts exerts their effects by accumulating cytosolic β-catenin (Shimizu et al, 1997), our current observation that accumulation of β-catenin inhibits chondrogenesis is in agreement with the inhibition of chondrogenesis by the transforming Wnts (Rudnicki and Brown, 1997;Stott et al, 1999;Tufan and Tuan, 2001). Although no direct evidence for the role of β-catenin in chondrogenesis is yet available, Hartmann and Tabin (Hartmann and Tabin, 2000) reported that misexpression of β-catenin in developing chicken wing buds accelerates chondrocyte maturation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Because the transforming group of Wnt family, such as Wnt1 and Wnt7a, but not nontransforming Wnts exerts their effects by accumulating cytosolic β-catenin (Shimizu et al, 1997), our current observation that accumulation of β-catenin inhibits chondrogenesis is in agreement with the inhibition of chondrogenesis by the transforming Wnts (Rudnicki and Brown, 1997;Stott et al, 1999;Tufan and Tuan, 2001). Although no direct evidence for the role of β-catenin in chondrogenesis is yet available, Hartmann and Tabin (Hartmann and Tabin, 2000) reported that misexpression of β-catenin in developing chicken wing buds accelerates chondrocyte maturation.…”
Section: Discussionsupporting
confidence: 83%
“…The expression of N-cadherin is downregulated in the later stage of chondrogenesis, which appears to be required for the progression of precartilage condensation to cartilage nodules (Oberlender and Tuan, 1994;Chang et al, 1998;Oh et al, 2000;Yoon et al, 2000). The involvement of β-catenin in the regulation of chondrogenesis has been suggested from the observation that ectopic expression of members of Wnt genes such as Wnt1, Wnt7a and Wnt14 (Rudnicki and Brown, 1997;Hartmann and Tabin, 2001;Tufan and Tuan, 2001;Tufan et al, 2002a) or frizzled receptor for Wnt (Tufan et al, 2002b) Expression of N-cadherin and α-catenin was determined by western blotting (top). Chondrocytes were untreated (Con) or treated with 1 µM RA or 5 ng/ml IL1β for 72 hours.…”
Section: Discussionmentioning
confidence: 99%
“…This finding also suggests that GSK-3␤ inhibition is more important during early chondrogenesis, supporting our results that introduction of both wild-type and ⌬GSK-3␤ affects younger rather than older cultures during BMP-2-mediated chondrogenesis. Wnt-3A overexpression in C3H10T1/2 micromass cultures also regulates the level of Ncadherin protein, supporting the postulate that Wnts act, at least in part, via regulating cadherin levels (27,37,54). Previously we have observed that overexpression of both wild-type and mutant N-cadherin disrupts BMP-2-induced chondrogenesis (5), indicating that tight regulation of Ncadherin is required for the correct series of event to move mesenchymal cells through condensation to differentiation.…”
Section: Discussionmentioning
confidence: 63%
“…We have observed that BMP-2-induced chondrogenesis in C3H10T1/2 cells is accompanied by down-regulation of Wnt-7A and up-regulation of Wnt-3A, whereas the level of other Wnts, including Wnt-3 and Wnt-5A, remains unchanged (22). This observation raises the intriguing possibility that BMP-2-mediated mesenchymal chondrogenesis results from the regulated, antagonistic relationship between the chondro-inhibitory Wnts, such as Wnt-7A (26,27), and chondro-enhancing Wnts. Such a scenario in the developing vertebrate limb would thus bear some analogy to the interactive relationship between the actions of decapentaplegic (a BMP homolog) and Wingless (a Wnt homolog), which synergistically regulate a number of developmental and patterning events in Drosophila (39,40,44).…”
mentioning
confidence: 99%
“…Here, N-cadherin has a role in the cellular condensation (Tuan, 2003), being a direct target of SOX9, a transcription factor that is essential for chondrocyte differentiation and cartilage formation (Panda et al,2001). Misexpression of wnt7a (wingless/int, a chondro-inhibitor in vitro) in mesenchymal chondrogenic cultures directly led to prolonged expression of N-cadherin, stabilisation of N-cadherin mediated cell-cell adhesion and eventual inhibition of chondrogenesis (Tufan and Tuan, 2001;Tufan et al, 2002). Ncadherin mRNA levels increase during osteogenic and myogenic differentiation and decrease during adipogenic differentiation.…”
Section: N-cadherin Expression From Embryo To Adultmentioning
confidence: 99%